2013
DOI: 10.1088/0004-637x/777/1/43
|View full text |Cite
|
Sign up to set email alerts
|

Clash: Complete Lensing Analysis of the Largest Cosmic Lens Macs J0717.5+3745 and Surrounding Structures

Abstract: The galaxy cluster MACS J0717.5+3745 (z = 0.55) is the largest known cosmic lens, with complex internal structures seen in deep X-ray, Sunyaev-Zel'dovich effect and dynamical observations. We perform a combined weak and strong lensing analysis with wide-field BV R c i z Subaru/Suprime-Cam observations and 16-band Hubble Space Telescope observations taken as part of the Cluster Lensing And Supernova survey with Hubble (CLASH). We find consistent weak distortion and magnification measurements of background galax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
135
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(145 citation statements)
references
References 154 publications
(228 reference statements)
10
135
0
Order By: Relevance
“…The first conclusion we can derive from these results is that the mass distribution shows multiple distinct concentrations as shown in Figures 4 and 5. Earlier work has generally claimed 4 peaks in this region (Ma, Ebeling & Barrett 2009;Limousin et al 2012;Medezinski et al 2013). A more precise picture of the location of our peaks can be seen in figure 9 below.…”
Section: Dark Matter Distributionmentioning
confidence: 52%
See 3 more Smart Citations
“…The first conclusion we can derive from these results is that the mass distribution shows multiple distinct concentrations as shown in Figures 4 and 5. Earlier work has generally claimed 4 peaks in this region (Ma, Ebeling & Barrett 2009;Limousin et al 2012;Medezinski et al 2013). A more precise picture of the location of our peaks can be seen in figure 9 below.…”
Section: Dark Matter Distributionmentioning
confidence: 52%
“…Some systems in Z09 are updated with new spectroscopic redshifts from Limousin et al (2012); Schmidt et al (2014) and Vanzella et al (2014), and also some system definitions are improved following Limousin et al (2012), Medezinski et al (2013) and Richard et al (2014). System 2 was excluded in some previous analyses since this source was too faint.…”
Section: Lensing Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the large total mass ( = Ḿ 3.5 0. ; Umetsu et al 2014), complex mass distribution, and relatively shallow mass profile (Zitrin et al 2009), the cluster provides a large area of sky with high lensing magnificationand is thus selected as part of the Cluster Lensing And Supernova survey with Hubble (CLASH, Postman et al 2012;Medezinski et al 2013) and the HST Frontier Fields program 23 (Lotz et al 2014(Lotz et al , 2016 to find high-z lensed objects. Ma et al (2009) reported decrements in the ICM temperature near two of the subclusters of MACSJ0717.5+3745, which they interpret as remnants of cool cores.…”
Section: Introductionmentioning
confidence: 99%